1997
DOI: 10.1016/s0014-5793(97)00523-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker evidence of DNA oxidation in lung cancer patients: association of urinary 8‐hydroxy‐2′‐deoxyguanosine excretion with radiotherapy, chemotherapy, and response to treatment

Abstract: Ratios of urinary 8-hydroxy-2'-deoxyguanosine to urinary creatinine (8-OHdG/creatinine) have been considered as a good biological indicator of DNA oxidation. Urinary 8-OHdG/ creatinine levels of lung cancer patients were evaluated by enzyme-linked iramunosorbent assay using a monoclonal antibody N45.1 during radiotherapy and chemotherapy. An increase in urinary 8-OHdG/creatinine was found in non-small-cell carcinoma (non-SCC) patients during the course of radiotherapy. SCC patients showed higher levels of urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
166
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(173 citation statements)
references
References 18 publications
6
166
0
1
Order By: Relevance
“…Nevertheless, MDA excretion seems to be a reliable indicator for LCPUFA peroxidation, as there were no other differences in dietary intake according to the dietary protocols (data not shown). Measurement of urinary 8-OHdG has become a well accepted marker of oxidative DNA damage in the human body [15] and it has been measured by several methods such as gas chromatography with mass spectrometric detection [41] and HPLC with electrochemical detection (ECD) [20]. Recently, an ELISA based on monoclonal IgG (N45.1 clone) was developed for estimation of 8-OHdG in urine [15], which made urinary 8-OHdG measurement much easier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, MDA excretion seems to be a reliable indicator for LCPUFA peroxidation, as there were no other differences in dietary intake according to the dietary protocols (data not shown). Measurement of urinary 8-OHdG has become a well accepted marker of oxidative DNA damage in the human body [15] and it has been measured by several methods such as gas chromatography with mass spectrometric detection [41] and HPLC with electrochemical detection (ECD) [20]. Recently, an ELISA based on monoclonal IgG (N45.1 clone) was developed for estimation of 8-OHdG in urine [15], which made urinary 8-OHdG measurement much easier.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of urinary 8-OHdG has become a well accepted marker of oxidative DNA damage in the human body [15] and it has been measured by several methods such as gas chromatography with mass spectrometric detection [41] and HPLC with electrochemical detection (ECD) [20]. Recently, an ELISA based on monoclonal IgG (N45.1 clone) was developed for estimation of 8-OHdG in urine [15], which made urinary 8-OHdG measurement much easier. Yoshida et al [42] found a good correlation (r ¼ 0.88) between urinary 8-OHdG levels obtained with using ELISA (same kit as in our study) and HPLC-ECD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's reported that within 8OHdG viral genomes introduce G:C → T:A transitions in vivo [10,11]. Due to its mutagenic potential, 8OHdG has been widely suggested as a biomarker for various cancers [12][13][14]. The concentration of 8OHdG is also evaluated in smokers and non-smokers [9,15,16] since cigarette smoke contains a large amount of oxygen radical forming substances, such as catechol and hydroquinone that may enhance lung carcinogenesis by free radical-mediated reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of analytical methodologies for 8OHdG determination are more common than for 8oxoG, with many reports of 8oxoG being determined as 8OHdG. Elevated levels of 8OHdG have been correlated with exposure to ionizing radiation [8], industrial chemicals [9], air pollution [10], cigarette smoking [11], cancer [12,13], chemotherapy [14], and ischemia-reperfusion [15][16][17]. Although only a few are mentioned here, there are several hundred reports linking increased concentrations of 8OHdG to increased oxidative stress or disease states, with over twenty reports using 8OHdG as a biomarker for ischemia-reperfusion.…”
Section: Introductionmentioning
confidence: 99%